Impact of Factors on the Intention to Use Ride-hailing Technology Applications during the COVID-19 Epidemic in Vietnam - Mai, Nguyen Ngoc; Tháº£o, Nguyá»…n Thá»‹ Minh; Thuy, Vo Hoang Ngoc (International Review of Management and Marketing, 2021)
This article aims to define the intent to use ride-hailing technology applications in the current Covid-19 translation situation and related factors such as: The usefulness of ride-hailing application, the attractiveness of private cars, the influence of the subjective norms and perceived behavior control factor. The study surveyed 342 questionnaires in Vietnam with a Likert scale. Hypothesis testing in this study uses the validity test, reliability test, multiple linear regression analysis, and the correlation between factors with SPSS version 22.0. The research results show that all 4 factors have a positive influence on the intention to use ride-hailing applications. Of which, the the usefulness of ride-hailing application factor has the strongest impact on the intention to use ride-hailing technology apps, and the attractiveness of the private vehicle had the least influence on the intention to use ride-hailing technology applications during the Covid-19 season. Keywords: Ride-hailing technology applications, intention to use, the attractiveness of private cars, Covid-19, the usefulness of ride-hailing application. JEL Classifications: N70, N75, R41 DOI: https://doi.org/10.32479/irmm.10839